Interpretasi Masalah Psikososial Pada Anak Sekolah Dasar: Faktor Resiko Dan Protektif Yang Mempengaruhi Kesehatan Jiwa - Sumilat, Vervando; laka, Angela A. M. L; Wetik, Syenshie V. (STIKES Ngesti Waluyo, 2024)
Mental health issues that are not optimally addressed during childhood, particularly among elementary school-aged children, have a significant correlation with an increased risk of mental health problems in later stages of life, namely adolescence or young adulthood. Depression is the most common mental health issue experienced by children, followed by social, behavioural, and emotional disorders, anxiety, psychological distress, internet addiction, stress, social phobia, sexual and emotional abuse, violence, as well as attention deficit and hyperactivity disorders. The variety of mental health issues experienced by children highlights the importance of early attention and intervention to support healthy mental development and prevent long-term adverse effects. The purpose of this study is to provide an overview of the factors influencing the mental health of elementary school-aged children, including risk and protective factors. A quantitative descriptive study was conducted at SDN Inpres Kolongan, North Sulawesi, using a survey method on a population of 171 students aged 9-14 years, with total sampling resulting in 171 respondents. Data was collected using the Strength and Difficulty Questionnaire for Children (SDQC). The findings of this study revealed a significant